Facade flame depth coming out from the fire compartment opening subject the external sideward wind - Sun, Xiepeng; Yi, Jiwei; Han, Yu; Zhang, Xiaolei; Tang, Fei; Hu, Longhua (Energy (Oxford), 2024)
When a fuel leakage/energy release (i.e., combustion, fire) inside a compartment, the external facade flame characteristics through opening are of great significance for protecting human life and property, as well as assessment of its risk and impact to urban environment. This work investigates facade flame depth coming out from fire compartment opening with fuel combustion/energy release inside the compartment for under-ventilated condition under sideward wind, which is a fundamental parameter in describing facade morphological characteristics in particular building fire, meanwhile still no work can be found in previous studies. Results show that, as sideward wind speed increases, the flame depth first increases a bit then decreases significantly. A CFD simulation is carried out to understand flow field controlling facade flame depth under windless and sideward wind situations. A physical analysis is presented on account of mechanisms of complex interaction among sideward wind inertial, outflow momentum through opening, and flame buoyancy flux are proposed based on controlling mechanisms, which well represents the facade flame depth by a non-dimensional function under sideward wind condition. This study makes an important new contribution comparing with previous knowledge, and has potential practical value for fuel combustion inside confined space and the corresponding numerical model verification. [Display omitted] •Experiments on fuel combustion/energy release inside compartment with an opening.•Investigated the flame coming out from the fire compartment opening under the sideward wind.•Quantified facade flame depth for various external sideward wind speeds and energy release rate.•Proposed three characteristic length scales to represent the facade flame depth.•Proposed a physical model of facade flame depth with fuel combustion under sideward wind conditions.